2014
DOI: 10.1007/s00125-014-3187-y
|View full text |Cite
|
Sign up to set email alerts
|

A PGC-1α- and muscle fibre type-related decrease in markers of mitochondrial oxidative metabolism in skeletal muscle of humans with inherited insulin resistance

Abstract: These data indicate that inherited insulin resistance coincides with reduced mitochondrial oxidative capacity in a PGC-1α- and muscle fibre type-related manner. Whether this co-existence is directly or indirectly related to insulin resistance remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
4
22
2
Order By: Relevance
“…1A). This fiber type composition is in accordance with previous observations using (immuno)histochemistry (9-11,13-15,26) and biochemical methods (18,22). In the T2D group, MHC I, IIa, and IIx constituted 35, 45, and 20% (total 65% MHC II), respectively.…”
Section: Fiber Type Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…1A). This fiber type composition is in accordance with previous observations using (immuno)histochemistry (9-11,13-15,26) and biochemical methods (18,22). In the T2D group, MHC I, IIa, and IIx constituted 35, 45, and 20% (total 65% MHC II), respectively.…”
Section: Fiber Type Compositionsupporting
confidence: 92%
“…Thus, it is likely that human type I fibers are more important than type II fibers for maintaining glucose homeostasis in response to insulin. Indeed, a decreased proportion of type I fibers has been found in various insulin resistant states such as the metabolic syndrome (9), obesity (13,14), T2D in some (10,13,14) but not all (12,15) studies and following bedrest (16), as well as in tetraplegic patients (17), and subjects with an insulin receptor gene mutation (18).…”
mentioning
confidence: 99%
“…Alleviating mitochondrial dysfunction may decrease cardiac I/R injury. Meanwhile, modulating mitochondrial function may improve insulin resistance and reduce subsequent cardiac mortality 23,24. In the present study, lin28a overexpression alleviated mitochondria ultrastructure impairment as demonstrated by intact membrane and cristae although still with a greater size after cardiac I/R in diabetic mice.…”
Section: Discussionsupporting
confidence: 53%
“…Finally, we performed a principal component analysis on the entire gene expression signature of our control and experimental samples (EPC, UASMC, iSMC) as well as control samples from previously published studies: Skeletal Muscle 24,25 , Brain 26 , Liver 26 , Umbilical Vein and Coronary Artery Endothelial Cells 27 , Aortic Smooth Muscle Cells 28,29 , Dermal Fibroblasts 30 . This analysis confirmed that the transdifferentiated iSMC closely resemble the control cells including adult aorta SMC and umbilical artery SMC while at the same time being significantly different from the starting EPC population (Figure 3G).…”
Section: Resultsmentioning
confidence: 99%